Role of IQGAP1 in endothelial barrier enhancement caused by OxPAPC - Tian, Yufeng (Am J Physiol Lung Cell Mol Physiol, 2016)
Oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphatidylcholine (OxPAPC) attenuates agonist-induced endothelial cell (EC) permeability and increases pulmonary endothelial barrier function via enhancement of both the peripheral actin cytoskeleton and cell junctions mediated by Rac1 and Cdc42 GTPases. This study evaluated the role for the multifunctional Rac1/Cdc42 effector and regulator, IQ domain containing GTPase-activating protein (IQGAP1), as a molecular transducer of the OxPAPC-mediated EC barrier-enhancing signal. IQGAP1 knockdown in endothelial cells by gene-specific small-interfering RNA abolished OxPAPC-induced enlargement of VE-cadherin-positive adherens junctions, suppressed peripheral accumulation of actin polymerization regulators, namely cortactin, neural Wiskott-Aldrich syndrome protein (N-WASP), and actin-related protein 3, and attenuated remodeling of the peripheral actin cytoskeleton. Inhibition of OxPAPC-induced barrier enhancement by IQGAP1 knockdown was due to suppressed Rac1 and Cdc42 activation. Expression of an IQGAP1 truncated mutant showed that the GTPase regulatory domain of IQGAP1 was essential for the OxPAPC-induced membrane localization of cortactin, adherens junction proteins VE-cadherin and p120-catenin, as well as for EC permeability response. IQGAP1 knockdown attenuated the protective effect of OxPAPC against thrombin-induced cell contraction, cell junction disruption, and EC permeability. These results demonstrate for the first time the role of IQGAP1 as a critical transducer of OxPAPC-induced Rac1/Cdc42 signaling to the actin cytoskeleton and adherens junctions, which promotes cortical cytoskeletal remodeling and EC barrier-protective effects of oxidized phospholipids.